Pengaruh Media Pembelajaran Video Animasi Edukatif Terhadap Hasil Belajar Ipas Siswa Kelas III MI Islahul Ikhwan NW Mispalah Praya - Andri Afriani; Bq. Indana Zulfa; Siti Ardila Hijriani (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aimed to examine the effect of educational animated video media on the learning outcomes of third-grade students in Natural and Social Sciences (IPAS) at MI Ishlahul Ikhwan NW Mispalah Praya. The study employed a quantitative approach using a **one-group pretest-posttest experimental design**. The participants consisted of all 24 third-grade students selected through a total sampling technique. Data were collected using IPAS achievement tests administered before (pretest) and after (posttest) the implementation of educational animated video media. The data were analyzed using descriptive statistics and the **Wilcoxon Signed Rank Test** because the data were not normally distributed. The findings revealed a significant improvement in students' learning outcomes, with the mean score increasing from 72.71 on the pretest to 85.62 on the posttest. The Wilcoxon Signed Rank Test yielded a significance value of 0.000 (p < 0.05), indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. These findings demonstrate that educational animated video media have a significant positive effect on students' IPAS learning outcomes. Therefore, teachers are encouraged to integrate this instructional media into classroom learning to enhance students' motivation, conceptual understanding, and overall academic achievement.